Trait Mindfulness, Resilience, Self-Efficacy, and Postpartum Depression: A Dominance Analysis and Serial-Multiple Mediation Model - Mei X; Mei R; Li Y; Yang F; Liang M; Chen Q; Ye Z (Psychology Research and Behavior Management)
Xiaoxiao Mei,1 Ranran Mei,2 Yan Li,1 Funa Yang,3 Minyu Liang,4 Qianwen Chen,4 Zengjie Ye5 1School of Nursing, Hong Kong Polytechnic University, Hong Kong, People’s Republic of China; 2Department of Breast Oncology, Guangzhou Institute of Cancer Research, The Affiliated Cancer Hospital, Guangzhou Medical University, Guangzhou, People’s Republic of China; 3Nursing Department, The Affiliated Cancer Hospital of Zhengzhou University and Henan Cancer Hospital, Zhengzhou, People’s Republic of China; 4School of Nursing, Guangzhou University of Chinese Medicine, Guangzhou, People’s Republic of China; 5School of Nursing, Guangzhou Medical University, Guangzhou, People’s Republic of ChinaCorrespondence: Zengjie Ye, Email zengjieye@qq.comBackground: Postpartum depression affects many women after childbirth, impacting both maternal and child well-being. Psychological traits such as trait mindfulness, resilience, and self-efficacy have been linked to postpartum depression, but their interactions and collective influence are not well understood.Objective: The study aims to examine the associations between trait mindfulness, resilience, self-efficacy, and postpartum depression.Methods: A cross-sectional survey was conducted from August 2022 to May 2023 using the Mindful Attention Awareness Scale, the 10-item Connor-Davidson Resilience Scale, the General Self-efficacy Scale, and the Edinburgh Postnatal Depression Scale. Dominance analysis, latent profile analysis, and serial-multiple mediation models were employed for data analysis.Results: Dominance analysis showed that trait mindfulness, resilience, and self-efficacy explained 36.3%, 35.4%, and 28.3% of the variance in postpartum depression, respectively. Three trait mindfulness profiles were identified as mild (23.2%), moderate (55.5%), and high (21.3%). Postpartum women in the mild group exhibited higher postpartum depressive symptoms than those in the moderate and high groups. The effects of trait mindfulness on postpartum depression were significantly mediated by resilience (B=− 0.064, 95% CI − 0.088 to − 0.044), self-efficacy (B=− 0.014, 95% CI − 0.023 to − 0.006), and serial mediation between resilience and self-efficacy (B=− 0.027, 95% CI − 0.040 to − 0.015). Similar significant mediation effects were observed for moderate (resilience: B=− 0.126, 95% CI − 0 .169 to − 0.065, self-efficacy: B=− 0.041, 95% CI − 0.078 to − 0.010, resilience and self-efficacy: B=− 0.053, 95% CI − 0.090 to − 0.023) and high trait mindfulness profiles (resilience: B=− 0.381, 95% CI − 0.514 to − 0.267, self-efficacy: B=− 0.082, 95% CI − 0.139 to − 0.033, resilience and self-efficacy: B=− 0.160, 95% CI − 0.237 to − 0.089) when compared to the mild reference group.Conclusion: Trait mindfulness significantly impacts postpartum depression and exhibits heterogeneity among postpartum women. The relationship between trait mindfulness and postpartum depression was mediated by resilience and self-efficacy.Keywords: postpartum depression, resilience, self-efficacy, trait mindfulness